1974
DOI: 10.1017/s0022143000023157
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Sliding of a Temperate Glacier

Abstract: Detailed measurements of the positions of stakes along the center-line of the lower Nisqually Glacier were made over a period of two years. Variations in the basal sliding speed were calculated from the measured changes in surface speed, surface slope, and thickness, using the glacier flow model of Nye (1952) and allowing for the effect of the valley walls, longitudinal stress gradients, and uncertainties in the flow law of ice. The flow is predominantly by basal sliding and has a pronounced seasonal variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(93 citation statements)
references
References 26 publications
7
86
0
Order By: Relevance
“…Kamb and others (1994) demonstrate that increases in basal water storage on the days-toweeks time-scale cause larger speeds on Columbia Glacier. It is likely that seasonal water-input changes on Columbia Glacier also cause speed cycles as they do on other glaciers (Hodge, 1974;Iken and others, 1983). Speed on Columbia…”
Section: Discussionmentioning
confidence: 98%
“…Kamb and others (1994) demonstrate that increases in basal water storage on the days-toweeks time-scale cause larger speeds on Columbia Glacier. It is likely that seasonal water-input changes on Columbia Glacier also cause speed cycles as they do on other glaciers (Hodge, 1974;Iken and others, 1983). Speed on Columbia…”
Section: Discussionmentioning
confidence: 98%
“…It should be noted, however, that borehole drilling through that glacier encountered basal debris and not clean bedrock (Harrison and others, 1986), so till deformation may have actually played a key role that surge. Hodge (1974) related water storage to seasonal velocity changes. Kamb and others (1994) also found that water storage was a good control variable for basal motion on shorter time scales, such as the speedup events on Columbia Glacier.…”
Section: Till Versus Bedrockmentioning
confidence: 99%
“…The predominance of cold ice in such glaciers suggests that supraglacialsubglacial hydrological connections are limited, and therefore that the hydrologically induced flow instabilities commonly observed on temperate glaciers (e.g. Hodge, 1974;Iken and Bindschadler, 1986;Willis, 1995) and mostly warm polythermal glaciers (e.g. Etzelmüller et al, 1993;Jansson, 1996;Kavanaugh and Clarke, 2001) are unlikely.…”
Section: Introductionmentioning
confidence: 99%